Carbon reserves in coffee agroforestry in the Peruvian Amazon - Geomar Vallejos-Torres; Nery Gaona-Jimenez; Roger Pichis-García; Luis Ordoñez; Patricia García-Gonzales; Aníbal Quinteros; Andi Lozano; Andi Lozano; Jorge Saavedra-Ramírez; Juan C. Tuesta-Hidalgo; Keneth Reategui; Wilder Macedo-Córdova; et al. (Frontiers in Plant Science)
IntroductionSecondary forests and coffee cultivation systems with shade trees might have great potential for carbon sequestration as a means of climate change adaptation and mitigation. This study aimed to measure carbon stocks in coffee plantations under different managements and secondary forest systems in the Peruvian Amazon rainforest (San Martín Region).MethodsThe carbon stock in secondary forest trees was estimated using allometric equations, while carbon stocks in soil, herbaceous biomass, and leaf litter were determined through sampling and laboratory analysis.ResultsThe biomass carbon stock in secondary forests was 132.2 t/ha, while in coffee plantations with Inga sp. shade trees was 118.2 t/ha. Carbon stocks were 76.5 t/ha in coffee with polyculture farming, while the lowest amount of carbon was found in coffee without shade trees (31.1 t/ha). The carbon sequestered by coffee plants in all agroforestry systems examined had an average of 2.65 t/ha, corresponding to 4.63 % of the total carbon sequestered, being the highest stored in the coffee system with Inga sp. shade trees. A higher content of glomalin-related soil proteins (GRSP) was found in coffee without shade trees, with 18.5 mg/g.DiscussionThese results point to Inga sp. as a compatible model of shade system for coffee farms. However, broader-scale time-average measurements and carbon dioxide emissions should be assessed in these study systems to have a full understanding of their climate impacts.